Moderasi Preferensi Risiko Pada Hubungan Kualitas Pelayanan Account Representative dan Kepatuhan WPOP - Ayu Disnayanti, Ni Kadek; Agung Pradnya Dewi, I.G.A (E-Jurnal Akuntansi; Vol 26 No 2 (2019), 2019)
This study aims to determine the effect of account representative service quality on individual taxpayer compliance with risk preferences as a moderating variable at the East Denpasar Primary Tax Office. The population in this study were all individual taxpayers registered at the East Denpasar Primary Tax Office. The number of samples used in this study is as many as 100 respondents from 76,543 population of individual taxpayers who are still effective in the Pratama Tax Office East Denpasar in 2017. The size of the sample is calculated based on Slovin formula with accidental sampling method sampling technique. Data collection in this study was conducted by questionnaire method. The data analysis technique used is moderated regression analysis (MRA). The results showed that account representative service quality had a positive effect on individual taxpayer compliance and risk preferences weakened taxpayer compliance with personal persons. Keywords: Service quality, risk preference, tax compliance